The Challenge of Evaluating by Competences in Higher Education. Reflections and Practical Experiences - Miguel A. Zabalza; Laura Lodeiro Enjo (Universidad Autónoma de Madrid, 2019)
The purpose of this article is to reflect about the assessment by competences at the university. It consists of two parts. In the first one, the meaning and didactic conditions applicable to each of the three central concepts that organize our contribution (assessment, competence and assessment by competences) are analyzed. In the second part, two concrete experiences of evaluation by competences in our universities are presented: one in which competences are linked to the various subjects of the curriculum; another one in which the assessment of the competences appears at the end of the career as an expression of the global training received: the ECOEs of the Faculties of Medicine.